A systematic review of late-life spousal bereavement and widowhood, with an emphasis on immigrants in western countries, and older Chinese adults. Issue 3 (2nd September 2018) - Wang, Qianyun; Walsh, Christine Ann; Tong, Hongmei
ABSTRACT: Spousal bereavement becomes increasingly common among older-aged individuals, posing considerable challenges to adults in late life. Immigrants, and older Chinese immigrants to Western countries, specifically may experience heightened negative outcomes as a consequence of spousal bereavement, due to migratory stress and marginalisation. This systematic review aims to summarise the research literature on spousal bereavement and/or widowhood in late life, with an emphasis on immigrants to Western countries in general and older Chinese adults. The paucity of spousal bereavement adjustment studies on older immigrants, and specifically on older Chinese immigrants, highlights the need for further research on this topic in order to inform the development of culturally sensitive interventions for social work services for this population.